LC–MS determination of triazolam and its hydroxy metabolites in mouse dried blood spots: application to transgenic mouse pharmacokinetic studies. (July 2017) - Kole, Prashant; Rao, Abhijith; Kurawattimath, Vishwanath; Mandlekar, Sandhya
Aim: The objective of this study was to develop a LC–MS/MS method for the simultaneous determination of triazolam (TRZ) and its two hydroxy metabolites in transgenic mouse dried blood spots (DBS) using BALB/c mouse blood as a surrogate biomatrix.Methodology/Results: The DBS method involved spotting volume of 10 μl using Ahlstrom 226 sample collection cards. A 'whole spot' analysis (6-mm punch) involved extraction of analytes using water and acetonitrile containing an internal standard. DBS samples were analyzed by a validated LC–MS/MS method with a run time of 4 min.Conclusion: This validated LC–MS/MS method using DBS extraction was applied to quantitation of TRZ, α-hydroxytriazolam and 4-hydroxytriazolam in a CYP3A4 transgenic mouse oral pharmacokinetic study of TRZ.